Nitrogen removal from digested piggery wastewater using fermented superphosphate within the pretreatment stage and an MAP fertilizer pot test. (1st March 2019) - Luo, Zifeng; Wang, Dehan; Yang, Jie; Huang, Honghui; Su, Guanyu
Abstract: Due to the shortage of land resources in southern China, digested piggery wastewater needs to be treated before it can be discharged. However, the digested piggery wastewater often has low C/N and poor biodegradability. It is usually used to reduce NH3 -N by a magnesium ammonium phosphate process, which is beneficial to the subsequent biological treatment, and the partial recovery of nitrogen and phosphorus forms the byproduct struvite. This research was based on fermented superphosphate to investigate how different amounts of fermented superphosphate, initial pH values and reaction times affect the recovery of nitrogen and phosphorus. The fertilizer effect of the recovered product was studied by pot tests, and the structure and composition of the recovered product were characterized by scanning electron microscopy (SEM) and X-ray diffraction (XRD). The results of the study showed that the chemical oxygen demand (COD)/TN ratio of the added fermented superphosphate MAP pretreatment (FSP/MAP) increased from 0.40 to 1.80, which improved the biodegradability in the subsequent biological treatment. The NH3 -N removal percentage after pretreatment with added fermented superphosphate (FSP) was 50.30%, which was 8.9% higher than that of ordinary phosphate fertilizer (SP). The optimum addition of FSP was 30 g L −1, the optimal initial pH was 9.5, and the optimal reaction time was 0.5 h. In the subsequent biological treatment, the denitrification effect of FSP/MAP-sequencing batch reactor (SBR) was significantly better than that of SP/MAP-SBR. In the pot experiment, the biomass of FSP/MAP corn in the aboveground and underground parts increased by 30.79% and 21.24%, respectively, and the fertilizer efficiency was significantly better than that of SP. The SEM and XRD analysis showed that the FSP/MAP fertilizer contained a large amount of struvite crystals and that the FSP/MAP fertilizer was a high-quality compound phosphate fertilizer. Graphical abstract: Highlights: Fermented superphosphate is used as phosphorus source for pretreatment, contains water-soluble phosphorus and DOC. Fermented superphosphate provides carbon source for subsequent SBR biological treatment processes. Pot test shows that the recycled product is high-quality phosphate fertilizer.